Functionalization of Poly[1-Vinyl (2-Pyrrolidone)] with Permanganate: Preparation and Application as a New Polymeric Oxidizing Reagent - ZACHARIAS, JOSE; RAJASEKHARAN PILLA, V.N. (Asian Journal of Chemistry, 2010)
Poly [1-vinyl(2-pyrrolidonium permanganate)] was prepared from NN' -methylene-bis-acrylarnide (NNMBA)-crosslinked poly( 1-vinyl 2-pyrrrolidone) resins by reaction with KMnO4. The insoluble polymeric reagent with a capacity of 2.6-5 mequiv of permanaganatelg was used for the oxidation of alcohols to carbonyl compounds. It possesses the desired characteristics of the polymeric reagents including filterability, operational simplicity, possibility of automation and reusability. The effects of solvent, duration of reaction and molar excess on the oxidation reactions were investigated to optimize the conditions for effective oxidations. The reagent can be stored for months without any loss of activitv. The capacity and efficiency of the reagent were found to be practically unchanged even after several cycles of operation.